Characterization of children under five with severe protein-energy malnutrition treated in a clinic in Timor Leste - Anagalys Ortega Alvelay; Marcos Félix Osorio Pagola; Denis Monzón Vega; Mabel Vega Galindo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: protein-energy malnutrition is a very common condition in third world countries. In children morbidity and mortality associated with it have increased. Objective: to characterize children with severe protein-energy malnutrition treated at a clinic in Timor Leste in the period from january to june 2009. Methods: an observational, descriptive, prospective, cross-sectional study conducted in all children under 5 years old who attended consultation during that period. Inclusion and exclusion criteria were applied. To obtain the data an examination, a clinical and nutritional assessment and a review of the medical records was performed for each patient. Results: the most affected age group was from 0 to 2 years old (61, 3 %) with a predominance of females (57 %). The predominant type of malnutrition was marasmus (66,7 %), which predominated in children from 0 to 2 years old (68,6 %), whereas in children suffering from kwashiorkor the predominant age group was from 3 to 5 years old (53,4 %). The non-measurement at birth was more frequent (50, 6 %), as well as the improper weaning (in 91, 6 % of the cases) and the sustained breastfeeding beyond six months of age observed in 96, 4 % of children. Conclusion: the age group from 0 to 2 years old, female sex, improper weaning and breastfeeding maintained after six months of age were predominant. A relationship between age, weaning and breastfeeding for the type of malnutrition with a reliability of 99 % was found.